2007
DOI: 10.1016/j.jhydrol.2007.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Thermal plume transport from sand and gravel pits – Potential thermal impacts on cool water streams

Abstract: Potential thermal impacts from below-water-table aggregate extraction on a coolwater stream were investigated by monitoring thermal plumes, moving through an unconfined glacial-outwash aquifer, and assessing their subsurface persistence. The growing demand for aggregate and increased pressure to pursue extraction in ecologically sensitive areas has driven the need for this work. During a 10-year period, ground and surface water temperatures were measured monthly, including two periods of intensive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 139 publications
(185 reference statements)
1
15
0
Order By: Relevance
“…The modification occurs because of the heat exchange between water and rock, causing both damping (i.e., decrease in signal amplitude) and retardation (i.e., time lag of the signal) of recharge . Studies have also demonstrated thermal damping and retardation in porous media (e.g., Molson et al, 1992;Palmer et al, 1992;Markle and Schincariol, 2007) and fractures (e.g., Molson et al, 2007). The nonconservative nature of water temperature, even within fairly large conduits, facilitates estimates of conduit size via an analysis of input and output thermographs Luhmann et al, 2012;Birk et al, 2014).…”
Section: A J Luhmann Et Al: Thermal Damping and Retardation In Karmentioning
confidence: 99%
“…The modification occurs because of the heat exchange between water and rock, causing both damping (i.e., decrease in signal amplitude) and retardation (i.e., time lag of the signal) of recharge . Studies have also demonstrated thermal damping and retardation in porous media (e.g., Molson et al, 1992;Palmer et al, 1992;Markle and Schincariol, 2007) and fractures (e.g., Molson et al, 2007). The nonconservative nature of water temperature, even within fairly large conduits, facilitates estimates of conduit size via an analysis of input and output thermographs Luhmann et al, 2012;Birk et al, 2014).…”
Section: A J Luhmann Et Al: Thermal Damping and Retardation In Karmentioning
confidence: 99%
“…At the Central Delhi Site, in contrast, the observed minimum/maximum peaks at 10 m bgl are most pronounced in February/September (8 months after the peaks in the river). Assuming a typical thermal retardation factor around 2 for sand aquifers (Markle and Schincariol 2007), travel time from Yamuna to the shallow piezometers can be estimated to be in the range of a few weeks at Palla and several months at Central Delhi.…”
Section: Temperature Profilesmentioning
confidence: 99%
“…Many studies have indicated that groundwater flow does not get sufficient attention during the design of closed geothermal systems (Chiasson et al 2000;Diao et al 2004;Ferguson 2009;Haehnlein et al 2010;Molina-Giraldo et al 2011). Field studies using heat as a tracer under natural gradient conditions (Palmer et al 1992;Markle and Schincariol 2007) have shown that advection should be expected in some hydrogeological settings. Failure to account for advection can cause inefficiencies in system design and operation.…”
Section: Introductionmentioning
confidence: 99%